Spatial analysis of chemical bombardment on Khushnaouti Valley and its demographic effects: (Balissan district as an example) - Sakar Mohammed Hasan; Tanka Osman Saeed; Fatimah Qader Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Balisan and Sheik wassan were the first two villages in Iraqi Kurdistan to be attacked by poison gas. The Iraqi attack on that valley in the period between (16/4/1988 to 31/7/1988), was a set of crimes against humanity and humanity, in which a sovereign state uses chemical weapons against its people. Shocked villagers who survived the attack likened the experience to watching doomsday. Even after this horrific gas attack on the area, the survivors were imprisoned in Erbil without medical treatment, dozens of Balisan villagers, dying within a week of their arrival. This research consists of a preface, containing a historical overview of the study area. Chemist in Kurdistan. As for the second chapter, it studied a geographical analysis of the chemical bombardment of the study area and its effects on the residents and people of Khoshnawaty Valley, and it also deals with the reasons and objectives of the defunct regime for perpetrating this crime, with reference to some health diseases and the emergence of some symptoms of disease for the residents of the area.